Studi terhadap prestasi pompa hidraulik ram dengan variasi beban katup limbah - Yosef Agung Cahyanta; Indrawan Taufik (Department of Mechanical Engineering, University of Udayana, 2008)
People who live far away from the water source have a problem to get water. Usually they use centrifugal pump to pumping the water to their house. Using this pump needs electricity, but some times they have problem with electricity. Hydraulic ramp pump is the solution because it doesn’t need electricity or fuel. Hydraulic ramp pump can work continuously 24 hours/day. Hydraulic ramp pump is cheaper and easy to build. This experiment has done to know the performance of the hydraulic ramp pump using the weight of waste valve variations and the head input. The hydraulic ramp pump use on this experiment has 1,5 inch inlet pipe and 0,5 inch outlet pipe. The variations of the waste valve weight are 410 g, 450 g, 490 g, 540 g, 580g and 630 g. The result of investigation shows that the maximum flow capacity, the maximum head discard and the maximum efficiency are obtained when the weight of the waste valve is 410 g. The maximum flow capacity is 11,146 × 10-5 m³/s, the maximum head discard is 7,378 m and the maximum efficiency is 16,302 %.